Formation and disintegration investigation of fivefold annealing twins in copper nanoparticles. (August 2019) - Deng, Ziliang; Luo, Jun; Yuan, Wenjuan; Xi, Wei
Abstract: Fivefold annealing twins (FAT) have been assumed to form by grain boundary migration according to the Ashby model. However, the mechanism of boundary migration lacks experimental support. Moreover, the FAT disintegration process has never been reported. In our experiment, the complete formation and disintegration process of FAT in copper nanoparticles was investigated by in-situ transmission electron microscopy with high temporal and spatial resolution. The results show that FAT formation and disintegration arises from the layer-by-layer migration of twin boundaries, induced by partial dislocation emission. This experimental observation is significant to the basic understanding of twinning mechanisms. Graphical abstract: Unlabelled Image